Hugging the Shore: Tackling Marine Carbon Dioxide Removal as a Local Governance Problem - Lezaun, Javier (Frontiers in Climate, 2021)
This Perspective explores the local governance of ocean-based carbon dioxide removal (CDR). Proposals to enhance the ability of oceans and marine ecosystems to absorb atmospheric CO2 are often discussed as examples of “geoengineering,” but this framing obscures the site-specific nature of most of the suggested intervention. The Perspective outlines some of the key local dimensions of marine CDR as currently imagined, and suggests a framework for increasing local participation in the assessment of these climate interventions. Robust processes of local participation are essential if we are to address the place-based conflicts that are bound to emerge if any of the proposed methods of CO2 removal is ever deployed at scale.